Development and psychometric evaluation of the Pornography Purchase Task. (September 2018) - Mulhauser, Kyler; Miller Short, Emily; Weinstock, Jeremiah
Abstract: Excessive pornography use and hypersexuality are frequently evaluated via direct self-report of problem severity and negative consequences associated with these behaviors. These face-valid assessments may be less sensitive to problems of hypersexuality in persons with low insight into their condition or in persons with motivation to minimize the negative impact of their pornography use. Demand for addictive substances has been effectively evaluated through a behavioral economic framework using a hypothetical purchase task, in which respondents are asked to report their degree of engagement with the substance as the financial costs associated with use increase. The present study describes the development and psychometric evaluation of the Pornography Purchase Task (PPT), a novel hypothetical purchase task for internet pornography use, in both a general population sample of adults (Study 1) and a clinical sample of men seeking hypersexuality treatment (Study 2). Overall, results showed good test-retest reliability of the PPT and the exponential-demand equation provided an excellent fit to responses on the PPT. The demand characteristic Intensity was most strongly related to concurrent indicators of hypersexuality and differentiated participants in Study 1. A similar pattern of results was observed in Study 2, with markedly stronger associations between most measures of demand for pornography and measures of hypersexuality for persons with recent use of pornography. Research and clinical implications of the PPT are discussed. Highlights: The Pornography Purchase Task (PPT) is a novel measure of demand for pornography The PPT showed good reliability and validity overall The PPT was evaluated in a general population and a clinical sample Demand metrics were associated with indicators of hypersexuality